2021
DOI: 10.3390/ijms22115891
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Downregulates Autophagy through Accelerated Turn-Over of the Ulk-1 Complex in a Trabecular Meshwork Cells Strain: Insights on Steroid-Induced Glaucoma Pathogenesis

Abstract: Steroid-induced glaucoma is a severe pathological condition, sustained by a rapidly progressive increase in intraocular pressure (IOP), which is diagnosed in a subset of subjects who adhere to a glucocorticoid (GC)-based therapy. Molecular and clinical studies suggest that either natural or synthetic GCs induce a severe metabolic dysregulation of Trabecular Meshwork Cells (TMCs), an endothelial-derived histotype with phagocytic and secretive functions which lay at the iridocorneal angle in the anterior segment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…The mechanism of injury caused by GCs to BMECs is not clear. Sbardella et al found that dexamethasone inhibited trabecular meshwork cells by downregulating autophagy, a kind of secretory endothelial cell similar to BMECs, causing metabolic disorder and even apoptosis [27]. Under normal circumstances, autophagy is at a low level, and only moderate autophagy has a protective effect.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of injury caused by GCs to BMECs is not clear. Sbardella et al found that dexamethasone inhibited trabecular meshwork cells by downregulating autophagy, a kind of secretory endothelial cell similar to BMECs, causing metabolic disorder and even apoptosis [27]. Under normal circumstances, autophagy is at a low level, and only moderate autophagy has a protective effect.…”
Section: Discussionmentioning
confidence: 99%
“…In a rat glaucoma model, neurosteroids induced the autophagy pathway to protect retinal neurons via GABRs/GABAA receptors [ 216 ]. However, another study reported that steroid therapy in the eye leads to the dysregulation of TMCs and glaucoma pathologies by inhibiting the autophagosome biogenesis pathway [ 217 ]. More studies are needed to conclude the effect of steroids on retinal neurons.…”
Section: Effects Of Autophagic Inducers and Inhibitors On Retinal Degenerative Diseasesmentioning
confidence: 99%
“…More and more studies have shown that autophagy is closely related to the occurrence and development of SIONFH (21). It has been reported that excessive use of glucocorticoids can lead to autophagy disorders (22). Autophagy, as one of the forms of eukaryotic programmed cell death (type II programmed cell death), can help the body to remove useless and broken organelles, harmful macromolecules, and pathogenic microorganisms (23).…”
Section: Discussionmentioning
confidence: 99%